Activity of 70% Ethanol Extract of Chrysophyllum cainito in Increasing Vertebrae Trabecular Bone Density in Female Mice - Nur Imamah Utaminingtyas; Burhan Ma'arif; Dewi Sinta Megawati; Ria Ramadhani Dwi Atmaja (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
Phytoestrogens are a class of compounds that have estrogen-like functions or structure. This research was conducted to find out the phytoestrogens activity in Chrysophyllum cainito leaves, in increasing the vertebrae trabecular bone density of female mice, using dexamethasone induction as osteoporosis model. The 70% ethanol extract of C. cainito leaves was given to female mice with dose of 100; 200; and 400 mg/kgBW mice/day after being induced orally with dexamethasone with 0.145 mg/kgBW mice/day. The positive control used was 1.3 mg/kgBW mice/day alendronate. This research had been done in four weeks. The increasing of trabecular vertebrae bone density of female mice was measured with Histomorphometry staining methods. The result showed the 70% ethanol extract of C. cainito leaves have activity in increasing trabecular vertebrae bone density for female mice with optimum dose of 400 mg/kgBW mice/day. This activity occurs because phytoestrogens content in 70% ethanol extract of C. cainito leaves, that may replace the function of estrogen in its bond with ER.